Horizons of enchantment : essays in the American imaginary - Johannessen, Lene (Re-mapping the transnational., 2011)
This title is about the peculiar power and exceptional pull of the imaginary in American culture. Johannessen's subject here is the almost mystical American belief in the promise and potential of the individual.